Transcriptomic Analysis of a Susceptible African Maize Line to Fusarium verticillioides Infection - Humaira Lambarey; Naadirah Moola; Amy Veenstra; Shane Murray; Mohamed Suhail Rafudeen (Plants, 2020)
Maize (Zea mays L.) is a staple crop providing food security to millions of people in sub Saharan Africa. Fusarium verticillioides, an important fungal pathogen, infects maize causing ‘Fusarium Ear Rot’ disease, which decreases maize kernel yield and the quality of the crop harvested. Currently, no African maize line is completely resistant to infection by F. verticillioides. This study investigated an African maize line, Zea mays CML144, infected with F. verticillioides. Analysis of morphological characteristics showed significant differences between mock-infected and infected plants. RNA-sequencing (RNA-seq) was conducted on plants 14 days post-inoculation to identify differentially expressed genes (DEGs) involved in F. verticillioides infection. Analysis of RNA-seq data revealed DEGs that were both significantly up- and down-regulated in the infected samples compared to the mock-infected control. The maize TPS1 and cytochrome P450 genes were up-regulated, suggesting that kauralexins were involved in the CML144 defense response. This was substantiated by kauralexin analyses, which showed that kauralexins, belonging to class A and B, accumulated in infected maize tissue. Gene ontology terms relating to response to stimulus, chemical stimulus and carbohydrate metabolic processes were enriched, and the genes belonging to these GO-terms were down-regulated. Quantitative real-time PCR was performed on selected DEGs and measurement of phytoalexin accumulation validated the RNA-seq data and GO-analysis results. A comparison of DEGs from this study to DEGs found in F. verticillioides (ITEM 1744) infected susceptible (CO354) and resistant (CO441) maize genotypes in a previous study, matched 18 DEGs with 17 up-regulated and one down-regulated, respectively. This is the first transcriptomic study on the African maize line, CML144, in response to F. verticillioides infection.